Study on the Twist Compensation of Helical Gear Tooth Flanks and the Arc-shaped Worm Wheel Dressing Method - Fang Yi; Yang Jianjun; Wang Jianwen; Zhang Ling; Zhou Guojun; Su Jianxin (Jixie chuandong)
Aiming at the problem of tooth surface twist of helical gears with longitudinal tooth crowing caused by the worm wheel grinding method, an anti-twist grinding method using an arc-shaped worm wheel was proposed. First of all, based on the generating process of the double-parameter envelope, a spatial meshing coordinate system between the worm wheel and the helical gear was established to calculate the contact line. Then, the twist values at different tooth width positions were calculated. The relation between the pressure angle deviation and the position value of the worm wheel was established, and the calculation process of the arc shape of the worm wheel was performed. Finally, an example was presented to verify the anti-twist dressing method. Compared with the deviation of the gear flank, the twist was compensated by using the arc-shaped worm wheel. The feasibility of the anti-twist grinding method was verified.